General processes responsible for the space leader birth in streamer coronas of negative leaders. (24th November 2021) - Babich, Leonid; Kutsyk, Igor; Bochkov, Evgeniĭ; Köhn, Christoph; Neubert, Torsten
Abstract: Local section of one s treamer in the streamer coronas ahead of negative leaders of long laboratory sparks can develop into 'space leaders', called so because of their high conductivity and initially being unconnected to the main negative leader. Available data of experimental research do not allow reliably unveiling a mechanism causal to the space leader birth. We, here, discuss a hypothetical but general mechanism based, mostly, on thermodynamics. The plasma-chemistry processes in one of the streamers of the negative leader corona and Joule heating of the gas within the streamer channel are casual to a birth of a conducting area in this streamer at the strength of the ambient electric field less than the selfbreakdown magnitude of 30 kV cm −1 . Two conclusions follow from the analysis. First, sufficiently high ambient field strength E 0 is required to heat the gas to a temperature sufficiently high for a birth of the conducting area during the observed time t obs . Second, the current of one streamer does provide sufficient heating; for this, the being heated area is to be fed by a multitude of the streamer branches. We limit ourselves to considering processes responsible for a formation of hot conducting areas in the negative corona. We assume that the birth of the heated area in the streamer, start new streamers from its ends and further heating of this area occurs in some local domain where the field strength exceeds the mean magnitude 11 kV cm −1 in the leader corona. We, proceeding from the experimentally observed time t obs of 1 μ s, show that the minimal magnitude of the E 0 of 20 kV cm −1 in the being heated area is required to ensure the gas temperature of 2000 K fitting the t obs . To illustrate our conclusions, we, using simplified models, carry out simulations treating selfconsistently the evolution of the electric field and the associated plasma chemistry.